Pre-Service EFL Teachers’ Emotional Experiences and Emotion Regulation Strategies in Research - Ananda Sri Wahyuni; Lystiana Nurhayat Hakim; Sundari Purwaningsih (Universitas Islam Negeri Palopo, 2026)
This study examines the emotional experiences and emotion regulation strategies of 93 pre-service English as a Foreign Language (EFL) teachers at various Indonesian universities during their research process. Using a cross-sectional survey design, data were collected via an online questionnaire and analyzed using descriptive statistics. The findings revealed that emotional experiences varied across five research phases. Tired (mild-pleasant) was the most consistently reported emotion across all research phases, indicating persistent cognitive demands and mental fatigue. Distressed (intense-unpleasant) emerged as prominent in four phases, particularly during the middle and later stages, while frustrated (intense-unpleasant) appeared mainly during the literature review and final analysis. Conversely, calm (mild-pleasant) was more common during the early and methodological phases. Regarding emotion regulation strategies, participants predominantly employed emotion-focused coping mechanisms, with Brief COPE strategies (M = 3.95) being more prevalent than ERQ strategies (M = 3.87). The most frequently used strategies were Acceptance (80.6%), Religion (79.6%), and Positive Reframing (71%), reflecting culturally and spiritually grounded coping approaches. The study underscores the emotionally taxing nature of the research process for Indonesian pre-service teachers and highlights their predominant use of culturally inflected, emotion-focused strategies to manage academic stress, offering important implications for providing targeted emotional and supervisory supports. Practical implications for academic advisors to integrate motivational support, open communication, and constructive feedback to mitigate students’ mental fatigue throughout the research process. Keywords: Emotion Regulation Strategies; Emotional Experiences; Pre-service EFL Teachers, Thesis Research